Analisis Implementasi dan Pelaporan Corporate Social Responsibility Perum Perumnas - Cut Vifde Avriyani Siregar; Eko Ganis Sukoharsono (Jurnal Ilmiah Mahasiswa FEB, 2014)
It is inevitable that every activity of the company would have an impact on the environment, either positive nor negative impacts. Therefore, the company is obliged to take responsibility for the impact, especially for the company that makea negative impact on the environment around the company. At this time, the implementation of corporate social responsibility is not a new issue anymore. The existence of the impact had been demanding the company to take responsibility for it. Through the activities of the corporate social responsibility, companies are trying to balance the "3P", which are profit, planet and, people. The goal is the company should not only concern toget high profit, but also pay attention to the natural environment and social environment around the company's business activities. Therefore, this study aims to analyze what are the activities, and how Perumnas reporting corporate social responsibility activities. By obtaining primary data from interviews and secondary data from the company's annual report, researcherhope can perform in-depth analysis related to Perumnas’s corporate social responsibility activities. This study may contribute to provide information and also assist in revealing self-image of Perumnas.   Kata kunci: corporate social responsibility, reporting, activities, Perumnas.